2015
DOI: 10.1111/dme.12964
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of low‐carbohydrate diets in people with Type 2 diabetes

Abstract: Aims The efficacy of low-carbohydrate diets (LCD) in people with Type 2 diabetes has divided the nutrition community. This review seeks to re-examine the available data to clarify understanding.Methods A comprehensive search of databases was used to identify meta-analyses of LCD in Type 2 diabetes. To improve the quality of the studies analysed, the following inclusion criteria were applied: randomized control trials ≥ 4 weeks in people aged > 18 years with Type 2 diabetes; a carbohydrate intake ≤ 45% of total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 34 publications
3
67
0
5
Order By: Relevance
“…The excess reduction in HbA1c was correlated with the degree of carbohydrate restriction, a finding not reported earlier. A recent review of the literature26 did not perform meta-analysis of the available HbA1c data due to a large heterogeneity in the carbohydrate intake in the intervention groups, and other meta-analyses have either shown a numerically greater reduction in HbA1c,6 7 or no effect in type 2 diabetes 9…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The excess reduction in HbA1c was correlated with the degree of carbohydrate restriction, a finding not reported earlier. A recent review of the literature26 did not perform meta-analysis of the available HbA1c data due to a large heterogeneity in the carbohydrate intake in the intervention groups, and other meta-analyses have either shown a numerically greater reduction in HbA1c,6 7 or no effect in type 2 diabetes 9…”
Section: Discussionmentioning
confidence: 99%
“…Conclusions on the efficacy of LCD compared with HCD from recent reviews are thus conflicting with regard to glycemic control and weight loss 4–8. A very recent critical review based on predefined criteria9 found no evidence of any superiority of LCD compared with HCD.…”
Section: Introductionmentioning
confidence: 99%
“…Part of the confusion is due to the wide range of definitions for a low-carbohydrate diet (73,74). While benefits to low-carbohydrate diets have been described, improvements tend to be in the short term and, over time, these effects are not maintained (74)(75)(76)(77). While some studies have shown modest benefits of very low-carbohydrate or ketogenic diets (less than 50-g carbohydrate per day) (78,79), this approach may only be appropriate for short-term implementation (up to 3-4 months) if desired by the patient, as there is little longterm research citing benefits or harm.…”
Section: Carbohydratesmentioning
confidence: 99%
“…While carbohydrate restriction initially lowered weight and fat mass in obese humans, over time this effect diminished, and weight benefits were not maintained (Hashimoto et al, 2016). Moreover, a recent meta-analysis of randomized control trials for low carbohydrate diets in subjects with type 2 diabetes suggests that a low carbohydrate diet does not improve glycemic control or other metabolic outcomes (van Wyk et al, 2016). …”
Section: Dietary Composition – When Is a Calorie Not Just A Calorie?mentioning
confidence: 99%